2016
DOI: 10.1016/j.mehy.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine to decrease NLRP3-activated inflammation and improve obesity-related metabolic dysregulation

Abstract: Obesity is a major risk-factor for the development of insulin resistance, type 2 diabetes, and cardiovascular disease. Circulating molecules associated with obesity, such as saturated fatty acids and cholesterol crystals, stimulate the innate immune system to incite a chronic inflammatory state. Studies in mouse models suggest that suppressing the obesity-induced chronic inflammatory state may prevent or reverse obesity-associated metabolic dysregulation. Human studies, however, have been far less positive, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 101 publications
(103 reference statements)
0
40
0
3
Order By: Relevance
“…As obesity‐induced inflammation involves multiple complimentary and redundant inflammatory pathways, blocking a single cytokine (eg, IL‐1β or TNF‐α) may not be sufficient to induce clinically significant metabolic improvements. However, colchicine affects multiple proinflammatory cell types, cytokines, and pathways activated in obesity . Although we hypothesize that colchicine can improve metabolic dysregulation by its ability to impair NLRP3 inflammasome activation, its ability to block neutrophil diapedesis, promote M2 macrophage differentiation, reduce chemotactic and adhesion molecule production, and suppress superoxide production, potentially all contribute to its anti‐inflammatory and potentially prometabolic effects …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As obesity‐induced inflammation involves multiple complimentary and redundant inflammatory pathways, blocking a single cytokine (eg, IL‐1β or TNF‐α) may not be sufficient to induce clinically significant metabolic improvements. However, colchicine affects multiple proinflammatory cell types, cytokines, and pathways activated in obesity . Although we hypothesize that colchicine can improve metabolic dysregulation by its ability to impair NLRP3 inflammasome activation, its ability to block neutrophil diapedesis, promote M2 macrophage differentiation, reduce chemotactic and adhesion molecule production, and suppress superoxide production, potentially all contribute to its anti‐inflammatory and potentially prometabolic effects …”
Section: Discussionmentioning
confidence: 94%
“…One mechanism by which colchicine exerts its anti‐inflammatory effects is by inhibiting NLRP3 inflammasome formation and activation . A recent retrospective study suggested that among patients with gout, long‐term colchicine treatment may have glycaemic benefit; however, to date no randomized controlled trial (RCT) has investigated colchicine's long‐term effects on glucose metabolism in adults with obesity and metabolic syndrome (MetS) . We hypothesized that administration of colchicine to adults with MetS, but who had not yet developed type 2 diabetes, would improve their obesity‐associated metabolic and inflammatory dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine, which is historically used in the treatment of gout, has been shown to induce an anti‐inflammatory response through destabilization of MTs, which subsequently interferes with the assembly of the NOD‐like receptor pyrin domain containing 3 (NLRP3) inflammasome . Activation of the NLRP3 inflammasome within macrophages is commonly implicated in innate immune inflammatory response .…”
Section: Mt‐targeting Agents’ Potentiation Of Immune Response and Impmentioning
confidence: 99%
“…Colchicine, which is historically used in the treatment of gout, has been shown to induce an anti‐inflammatory response through destabilization of MTs, which subsequently interferes with the assembly of the NOD‐like receptor pyrin domain containing 3 (NLRP3) inflammasome . Activation of the NLRP3 inflammasome within macrophages is commonly implicated in innate immune inflammatory response . NLRP3 uses a mitochondrially bound adapter protein (apoptosis‐associated speck‐like protein) containing a caspase recruitment domain to recruit caspase‐1 to the complex, followed by autocatalytic processing and activation, ultimately facilitating the cleavage of proinflammatory cytokines IL‐1β and IL‐18 to their activated forms .…”
Section: Mt‐targeting Agents’ Potentiation Of Immune Response and Impmentioning
confidence: 99%
“…Один из основных механизмов действия колхицина связан с подавлением синтеза ИЛ1β за счет интерференции с ак-тивацией NALP3-инфламмасомы [43]. По данным иссле-дования LoDoCo (Low-Dose Colchicine trial), у пациентов со стабильной ИБС прием колхицина (0,5 мг/сут) в сочета-нии со стандартной терапией приводит к снижению часто-ты кардиоваскулярных катастроф [44].…”
Section: другие препаратыunclassified